Athletes’ basic psychological needs and emotions: the role of cognitive reappraisal - Robazza, Claudio; Morano, Milena; Bortoli, Laura; Ruiz, Montse C. (Frontiers in Psychology, 2023)
In sport, where high achievements are at stake, athletes often feel pressure and emotions that hinder their performance. Emotion regulation becomes essential for athletes to handle stress, achieve optimal performance, and enhance their overall well-being. To advance both research and practical applications, it is crucial to examine the antecedents of emotion regulation and the impact on emotions and other feelings associated with performance. Specifically, the purpose of this cross-sectional study was to examine the role of athletes’ emotion regulation strategies (i.e., cognitive reappraisal and expressive suppression) in the relationship between basic psychological needs satisfaction, emotions, and psychobiosocial experiences. The sample consisted of 424 competitive athletes (246 men and 178 women) involved in individual sports (n = 164; e.g., fencing, gymnastics, martial arts, swimming, and tennis) or team sports (n = 260; e.g., basketball, rugby, soccer, and volleyball), aged 16–36 years (M = 23.08, SD = 7.65). Their competitive experience ranged from 1 to 21 years (M = 9.71, SD = 6.34) at regional (71%), national (18%), or international (11%) level, and they practiced their sport on average 3.74 times a week (SD = 1.73). Participants completed measures of basic needs satisfaction (i.e., competence, autonomy, and relatedness), emotion regulation style, emotions, and psychobiosocial experiences. Structural equation modeling results showed that competence need satisfaction was positively associated with pleasant emotions and psychobiosocial experiences that are perceived as functional for performance, and negatively associated with a maladaptive emotion regulation style (i.e., expressive suppression) and unpleasant emotions. Relatedness need satisfaction was positively related to an adaptive emotion regulation style (i.e., cognitive reappraisal), pleasant emotions, and psychobiosocial experiences, and negatively related to expressive suppression and unpleasant emotions. Finally, mediation analysis showed positive indirect effects from autonomy and relatedness satisfaction to pleasant emotions and psychobiosocial experiences via cognitive reappraisal. Findings suggest that the satisfaction of athletes’ basic psychological needs of autonomy and relatedness is related to the experience of pleasant emotions and functional psychobiosocial states when they adopt an adaptive emotion regulation style.